Universities as a systemic factor of the socio-cultural space of the region - M. A. Tlevtsezheva (Вестник Майкопского государственного технологического университета)
Introduction. Universities occupy a central place in the culture of any civilization, accumulating the achievements of mankind in science and education. They form the core of the scientific community, preserving and passing on the accumulated knowledge to new generations. Their main goal is to train qualified specialists capable of developing society and moving progress forward. However, the activities of universities go far beyond simply teaching students. They actively influence public life, stimulate the creation of scientific communities, support innovative projects and the dissemination of advanced ideas. History shows that the most talented and active representatives of the intelligentsia traditionally gathered around universities. Many outstanding thinkers, writers, artists and politicians received their education in universities. Universities were the birthplace of many social movements, political parties and creative unions. The methodological basis of the research is based on general scientific methods of synthesis, analysis, generalization and systematization.The Research results. Identification of the key role of universities in the formation of the intellectual potential of society and ensuring sustainable development of the state and the entire world community.Discussion and conclusion. Today, despite the changes in the world, universities remain an important element of the cultural landscape of each country. They help to preserve national traditions, cultivate patriotism and shape the worldview of young people. Moreover, universities provide a link between generations, maintaining the continuity of knowledge and experience. It can be safely said that the quality of higher education reflects the general level of development of society. The stronger and more authoritative the universities, the higher the likelihood of a successful future for the country.